Annealing-free perovskite films by instant crystallization for efficient solar cells - Yin, Maoshu; Xie, Fengxian; Chen, Han; Yang, Xudong; Ye, Fei; Bi, Enbing; Wu, Yongzhen; Cai, Molang; Han, Liyuan (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
Organic-inorganic perovskite solar cells (PSCs) have attracted considerable attention around the world because they can be fabricated easily and inexpensively by solution-based processes. The key to the fabrication of high-performance PSCs is the crystallinity and morphology of the perovskite film, and thermal annealing is usually required to achieve a film with the necessary properties. Herein, we introduce a technique for instant crystallization of perovskite films without the need for thermal annealing. Specifically, a solution of methylammonium iodide and lead iodide was spin-coated onto a substrate, and ethyl acetate was dripped onto the film during spinning to induce instant crystallization of a CH 3 NH 3 PbI 3 perovskite film. The resulting crystalline film exhibited large crystal grains and a high carrier lifetime. PSCs fabricated with annealing-free films prepared by means of this technique exhibited performance comparable to that of PSCs fabricated with annealed films and showed much higher efficiency than did reference cells fabricated with annealing-free films. This new instant-crystallization technique offers a way to shorten the device fabrication time, which will reduce the cost of manufacturing efficient PSCs. Ethyl acetate (EA) is introduced in a one-step spin-coating method and can induce instant crystallization of perovskite films to create efficient thermal annealing-free perovskite solar cells.